Beverages – a scoping review for Nordic Nutrition Recommendations 2023 - Emily Sonestedt; Marko Lukic (2024)
In PressThis article has been accepted for publication and undergone full peer review. It has gone through copyediting and typesetting but not yet final proofreading. Although final publication galleys will be added at a later stage, this article is fully citable using the DOI number. Background: Coffee, tea, sugar-sweetened beverages (SSBs), and low- and no-calorie-sweetened beverages (LNCSBs) are generally frequently consumed in the Nordic and Baltic countries. These beverages have also been related to potential health effects. This scoping review describes the evidence for the role of coffee, tea, SSBs, and LNCSBs for health-related outcomes as a basis for setting and updating food-based dietary guidelines. We used evidence from several qualified systematic reviews (i.e. World Cancer Research Fund, US Dietary Guidelines Advisory Committee, European Food Safety Authority, and World Health Organization) and performed a search for additional systematic reviews. The evidence suggests that moderate coffee and tea consumption do not have long-term adverse health effects. The long-term favorable effects of coffee consumption are related to reduced risk of endometrial and liver cancer, type 2 diabetes, and cardiovascular deaths. However, results from randomized controlled trials (RCTs) suggest that coffee brews that are rich in diterpenes, such as boiled coffee, increase serum cholesterol concentrations. High caffeine intake in pregnancy is associated with higher risk of pregnancy loss, preterm birth, and low birth weight. High consumption of SSBs has been associated with increased risk of obesity, type 2 diabetes, hypertension, and cardiovascular disease, based on data from RCTs and prospective cohort studies. The consumption of LNCSBs may result in a small reduction in body weight in adults, likely mediated through the effect of reduced energy intake, but has neutral effects on other cardiometabolic risk markers using evidence from RCTs. However, evidence from observational studies indicates increased risk of cardiometabolic diseases among high LNCSB consumers. In conclusion, current evidence suggests that moderate coffee and tea consumption have no long-term adverse health effects. The evidence of beneficial effects of coffee consumption on liver and endometrial cancer risk, and some cardiovascular outcomes, comes from observational studies. High consumption of boiled coffee should be avoided due to negative effect on lipid profile. Pregnant women should not exceed the recommended daily dose of caffeine intake of 200 mg set by the European Food Safety Authority as a safe level for the fetus. There is some evidence on beneficial effect of black and green tea on blood pressure. High consumption of SSBs has consistently been associated with adverse health effects, which is mainly due to excess energy intake, and should be limited. The conflicting results from RCTs and observational studies regarding LNCSBs may be due to revere causation and should be explored further.